Time to redefine Myeloma. (27th July 2015) - Pratt, Guy; Bowcock, Stella; Chantry, Andrew; Cook, Gordon; Jackson, Graham; Lai, Maggie; Low, Eric; Mulholland, Nicola; Owen, Roger; Rabin, Neil; Ramasamy, Karthik; Snowden, John A; et al.
Summary In November 2014 the International Myeloma Working Group (IMWG) revised the definition of multiple myeloma, such that asymptomatic patients with newly diagnosed multiple myeloma without any of the traditional 'CRAB' (hypercalcaemia, renal impairment, anaemia, bone disease) end organ damage criteria but with one of three new criteria would be recommended to start treatment. Previously, the standard of care for such patients was expectant management. These three new criteria are: greater than 60% clonal plasma cells on bone marrow biopsy, a serum free light chain (sFLC) ratio of >100 (the involved sFLC must be >100 mg/l) and greater than one unequivocal focal lesion on advanced imaging (low dose whole body computerized tomography, magnetic resonance imaging, 18F fluorodeoxyglucose positron emission tomography). Although this would appear to affect a small number of patients, the impact of these changes are broad, leading to an increased use of advanced imaging, a debate around the management of patients previously diagnosed with smouldering myeloma, changed terminology and clinical trial design and an extension of the use of biomarkers. For the first time the philosophy of treatment in myeloma will change from treatment initiation only being triggered by overt end organ damage to an era where sub clinical risk factors will also be taken into account.